PERILAKU MILLENIAL DALAM SENI GRAFIS - FAHMI REZA PRATAMA, Drs. Irwan, M.Sn., Drs. Ariusmedi, M.Sn. (Universitas Negeri Padang, 2019)
The purpose of visualizing millennial behavior that provides social anxiety in one’s own life and community environment, through graphic arts separation techniques.The creation of works of art needs to do a variety of preparations, including making observations, information seeking, appreciation, contemplation, extracting references, and literacy related to the initial idea, as well as deepening marerial directly around the environment according to these problems.Through graphic art the writer develops in the form of art work, some works of art that have been presented are: two. Selfie, documentation, negligent, one apathy, two apathy, education, happy, communal, and exist.Keywords: Millennial Behavior In Graphic Arts.